(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Background. Aim of the current prospective study is to investigate and revise the basic information related to the coronary artery bypass graft (CABG) procedure, in an attempt to reevaluate the current Greek DiagnosisRelated Groups (DRGs) system. Methods. In a Greek academic cardiothoracic surgical department, implementing clinical therapeutic protocols, we prospectively recruited 75 patients planned to undergo elective CABG. All basic demographic, medical and perioperative data were gathered in an extensive database, so asto be compared with data predicted by the DRGs system. Clinical indicators of performance aiming towards quality control were: perioperative mortality, postoperative myocardial infarct, postoperative stroke, postoperative renal failure, total hospital length of stay, rate of reoperation and rate of readmission. Results. None of the study patients deceased. No cases of perioperative myocardial infarct, stroke or renal failure were observed. Two of the patients developed respiratory failure, and one was reoperated for the control of perioperative bleeding. There were no cases of readmission to the hospital. The total length of stay was longer than the DRGs prediction (mean 11.5 vs 7 days), owed partially to the preoperative stay (mean 3.18days) in the department, due to reasons of medical vigilance and organisatory problems that led to the postponement of the operation. Conclusions. A review of the CABG related DRGs in Greece seems appropriate, based on the findings of the current study, suggesting a longer than predicted hospital stay.